2010
DOI: 10.1088/0957-4484/21/8/085705
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic coupling on dielectric nanowire core–metal sheath composites

Abstract: We have developed dielectric core/metal sheath nanowire (NW) composites for surface-enhanced Raman scattering (SERS), in which an electroless (EL) Ag plating approach was employed. The NW surface was uniformly covered with a high density of 3D silver islands, having a diameter in the 20-30 nm range and spaced less than approximately 10 nm apart. In comparison with the silver deposition via e-beam evaporation, the EL coating approach has the advantage of full metal coverage of the NWs. This approach also provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Reports show that SERS performance could be augmented with increased roughness 18, 19. Compared to top‐down methods, bottom‐up non‐lithographic techniques such as nanowire array construction can provide even more increased roughness 20–23. Thus, herein proposed vertically aligned (VA) carbon nanotubes (CNTs) can offer an extremely dense and rough nanostructure as a viable template for the SERS substrate.…”
mentioning
confidence: 99%
“…Reports show that SERS performance could be augmented with increased roughness 18, 19. Compared to top‐down methods, bottom‐up non‐lithographic techniques such as nanowire array construction can provide even more increased roughness 20–23. Thus, herein proposed vertically aligned (VA) carbon nanotubes (CNTs) can offer an extremely dense and rough nanostructure as a viable template for the SERS substrate.…”
mentioning
confidence: 99%
“…[10,11] In this context, compared to top-down methods, bottom-up lithographyless fabrication techniques such as a nanowire array construction can provide much higher roughness, demonstrated by various nanowire-based SERS substrates. [12][13][14][15][16][17][18] It has also been reported that the crossings of separate nanowires (especially when they are in slight contact to one another) can result in great SERS enhancements. [19] In order to create a lot more nanowire junctions, each gold nanowire should become thinner.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, NWs used for surface-enhanced Raman scattering (SERS) are of significant interest since SERS spectra can provide trace level detection and a chemical fingerprint by which a molecule can be identified. Several NWs types have been used to investigate the SERS effect, including silver NWs [6,7], gold NWs [8], semiconductor NWs [9], and dielectric NWs [10][11][12]. It has been demonstrated that the geometry of the nanowires and the orientation of the molecules play an important role in the SERS process [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several NWs types have been used to investigate the SERS effect, including silver NWs [6,7], gold NWs [8], semiconductor NWs [9], and dielectric NWs [10][11][12]. It has been demonstrated that the geometry of the nanowires and the orientation of the molecules play an important role in the SERS process [10][11][12][13][14]. However, most of the reported NW structures were randomly distributed on a surface, where the largest SERS enhancements noted were in the NW crossing [10] and between the NW and the substrate [14].…”
Section: Introductionmentioning
confidence: 99%